Detecting hybrid admixtures through DNA analysis (2012)
This paper discusses the methodologies and application of DNA-based protocol for detecting hybrid admixtures in seed lots. Using microsatellite DNA markers, we successfully detected hybrid admixtures in Certified Seeds of ‘Mestizo 1’, ‘Mestiso 3’, and ‘Mestiso 7’. Four Certified Seed lots of hybrid seeds obtained from National Seed Quality Control Services (NSQCS) Region 2 (Isabela) and Region 11 (Davao) were analyzed through DNA-based after seed purity using markers RM110, RM234, RM171, and RM263. DNA fingerprints were detected in 8% non-denaturing polyacrylamide gels and ethidium bromide staining. Hybrid admixtures of seed lots from NSQCS Isabela were 6.4% and 10.9% for ‘Mestizo 1’ and ‘Mestiso 7’, respectively. Seeds obtained from NSQCS Davao showed 6.4% and 3.3% in Mestiso 3 and Mestiso 7, respectively. Contrary to results obtained using conventional methods, our data show that DNA-based methods are capable of differentiating true-to-type hybrids from no-hybrids.